Republican Vietnam, 1963-1975 war, society, diaspora - Luu, Trinh M.; Vu, Tuong, 1965- (Studies of the Weatherhead East Asian Institute, Columbia University., 2023)
English-language scholarship all too often dismisses South Vietnam as an American creation, a product of US imperialism. Republican Vietnam, 1963-1975 boldly upends this depiction, exposing a diverse and dynamic portrait of the Second Republic. In twelve essays, each based on original archival research, the volume brings to life the Second Republic in all its complexities, displaying how politicians, students, educators, publishers, journalists, musicians, religious leaders, businessmen, and ordinary citizens built a highly intricate society--with dazzling entrepreneurial zeal, an outspoken press, globally engaged religions, a vibrant intellectual and associational culture, and a level of artistic production that remains unmatched since the Vietnam War. That inspired and frenzied age, though short lived, held a resilient spirit that Vietnamese refugees have kept alive. The trove of vernacular music and print media, not to mention the many associations the Vietnamese diaspora founded, exemplify the republican values that once energized South Vietnamese culture. But this nuanced society has appeared in popular media and American scholarship as a hopelessly dependent nation, led by corrupt dictators beholden to US interests. In contrast to such negative stereotypes, this account situates South Vietnamese front and center as agents of their own histories. Republican Vietnam is the first collection of scholarly essays on the Second Republic since the end of the Vietnam War. It is also among the first to use republicanism as a lens to re-examine twentieth-century Vietnamese history, the Vietnam War, and the diaspora. The twelve essays together show how war, in tandem with external intervention, shaped South Vietnam's economy, culture, and the life of every individual and family. By featuring works from Vietnamese and Vietnamese diasporic studies, this text takes the important step of bridging the two fields, laying the foundation for cross-disciplinary projects in the future.